BRCAness is beneficial for indicating triple negative breast cancer patients resistant to taxane. Issue 7 (July 2016) - Ishikawa, T.; Narui, K.; Tanabe, M.; Kida, K.; Oba, M.S.; Yamada, A.; Ichikawa, Y.; Endo, I.
Abstract: Aim: Triple negative breast cancer (TNBC) is a heterogeneous disease and is associated with the cancer stem cell (CSC), basal-like, and BRCA1 function deficient (BRCAness) subtypes. We examined these 3 subtypes in TNBC and compared their chemosensitivity against anthracycline or taxane with a special attention to BRCAness. Methods: Sixty-six TNBC cases were obtained from a randomized phase II trial comparing TCx6 (TC6) with FEC-Docetaxel (FEC-D) as neoadjuvant chemotherapy. The core needle specimens before chemotherapy were used for subtyping. The basal-like and CSC subtypes were identified by immunohistochemistry; CK5/6 and EGFR staining for the basal-like subtype and ALDH1 staining for the CSC subtype. The BRCAness subtype was examined by Multiplex Ligation-dependent Probe Amplification (MLPA). Correlations between subgroups and pCR rates according to each regimen and subtype were examined. Results: The basal-like and BRCAness subtypes were significantly associated (p = 0.010) with the other subtypes, but not the CSC subtype. The pCR rates were higher with FEC-D than with TC6 in the basal-like (54.5% vs 14.3%, p = 0.081) and BRCAness (56.2% vs 16.7%, p = 0.030) subtypes. Both were not effective in the CSC subtype (18.2% vs 11.8%, p = 1.00). Conclusion: BRCAness identified by MLPA was practically useful for treatment selection for avoiding taxane. ALDH1 may be considered as a marker for the CSC subtype requiring novel agents.